PCs for dummies - Gookin, Dan (--For dummies, 2013)
The all-time bestselling PC reference, fully updated for the newest technologies! Previous editions of this fun and friendly PC guide have sold more than three million copies, making it the bestselling PC reference in the world. Dan Gookin, the author whose straightforward and entertaining style is the foundation of the For Dummies series, gives you the same easy-to-follow guidance in this edition, fully updated for Windows 8, using the cloud, and all the newest PC bells and whistles. It's perfect for the absolute beginner as well as for anyone switching to the latest hardware.